2018
DOI: 10.3791/56385
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation Signals in Rabbit Sclera As a Tool for Evaluation of Therapeutic Tissue Cross-linking (TXL) for Myopia

Abstract: Methods to strengthen tissue by introducing chemical bonds (non-enzymatic cross-linking) into structural proteins (fibrillar collagens) for therapy include photochemical cross-linking and tissue cross-linking (TXL) methods. Such methods for inducing mechanical tissue property changes are being employed to the cornea in corneal thinning (mechanically weakened) disorders such as keratoconus as well as the sclera in progressive myopia, where thinning and weakening of the posterior sclera occurs and likely contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Second harmonic generation (SHG) imaging exploits the coherent scattering event whereby two incident photons are converted into a single photon of half the original wavelength. SHG signal emission is an intrinsic property of biological materials containing large repetitive, noncentrosymmetric units that include collagen, and indeed SHG has been used extensively to probe the organisation of scleral collagen fibril bundles (Brown et al, 2007;Cone-Kimball et al, 2013;Jones et al, 2015;Keyes et al, 2011;Pijanka et al, 2012;Teng et al, 2006;Zyablitskaya et al, 2018) (see also Fig 1D). The ability of SHG to image large tissue volumes has enabled full 3D reconstructions of the ex vivo human ONH to be built (Winkler et al, 2010), while its application in monitoring real-time pressure-induced LC and PPS deformations (Midgett et al, 2018;Sigal et al, 2014a) is enhancing our understanding of the role of IOP in glaucoma biomechanics.…”
Section: Multiphoton Microscopymentioning
confidence: 99%
“…Second harmonic generation (SHG) imaging exploits the coherent scattering event whereby two incident photons are converted into a single photon of half the original wavelength. SHG signal emission is an intrinsic property of biological materials containing large repetitive, noncentrosymmetric units that include collagen, and indeed SHG has been used extensively to probe the organisation of scleral collagen fibril bundles (Brown et al, 2007;Cone-Kimball et al, 2013;Jones et al, 2015;Keyes et al, 2011;Pijanka et al, 2012;Teng et al, 2006;Zyablitskaya et al, 2018) (see also Fig 1D). The ability of SHG to image large tissue volumes has enabled full 3D reconstructions of the ex vivo human ONH to be built (Winkler et al, 2010), while its application in monitoring real-time pressure-induced LC and PPS deformations (Midgett et al, 2018;Sigal et al, 2014a) is enhancing our understanding of the role of IOP in glaucoma biomechanics.…”
Section: Multiphoton Microscopymentioning
confidence: 99%
“…More recently, crosslinking of scleral tissue has been proposed as a mechanism to treat myopia, although the data are limited. 10 , 18 It is important to understand how the sclera reacts to crosslinking. Here, we observed that the effects of crosslinking on permeability persist at a significant distance away from the treatment area.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in clinical and biochemical studies of the effects of corneal CXL, the direct nondestructive observation of morphologic features of corneas after CXL treatment without extrinsic labeling is necessary. To tackle this problem, in recent years, second harmonic generation (SHG) microscopy has become a valid alternative [15][16][17][18].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%